1985
DOI: 10.1159/000466398
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of IgG and Plasma Proteins in Factor VIII Preparations - a Possible Cause of Adverse Reactions

Abstract: IgG in factor VIII preparations was studied as a possible cause of adverse reactions following infusion of hemophiliacs. Thin-layer immuno-gel filtration analysis of nine products from seven firms demonstrated aggregated and monomeric IgG at highly variable amounts and proportions. These factor VIII products contained from 20 to 700 mg IgG per 1000 IU of factor VIII; IgG-fibrinogen complexes were demonstrated by doubleantibody testing. A relationship is suggested between aggregated IgG and/or IgG complexes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
2
3
1
Order By: Relevance
“…This improved purity has afforded the significant benefits of increased potency and better solubility, both of which are important to manu facturer and clinician. More than 95% of the IgG and IgM are removed with fibronectin in the glycine/NaCl super natant and the concentrations of these proteins in the final product (<0.1 mg/ml) are well below those found in inter mediate purity concentrates [27]. Reduction of IgG and IgM has not resulted in decreased anti-A, the concentra tion of which remains similar to what it was in our earlier intermediate purity concentrate (unpubl.…”
Section: Safety and Efficacysupporting
confidence: 73%
“…This improved purity has afforded the significant benefits of increased potency and better solubility, both of which are important to manu facturer and clinician. More than 95% of the IgG and IgM are removed with fibronectin in the glycine/NaCl super natant and the concentrations of these proteins in the final product (<0.1 mg/ml) are well below those found in inter mediate purity concentrates [27]. Reduction of IgG and IgM has not resulted in decreased anti-A, the concentra tion of which remains similar to what it was in our earlier intermediate purity concentrate (unpubl.…”
Section: Safety and Efficacysupporting
confidence: 73%
“…This is consistent with the identification in this study of fibrinogen and fibronectin as components of these HMW aggregates, in agreement with the results of Tho mas et al [11], who have recently reported that heat-in duced aggregation was greatly reduced in fibrinogen-poor concentrates. Wadsworth et al [12] detected both aggre gated IgG and IgG-fibrinogen complexes in a range of commercial FVIII preparations, but neither the data pre sented here nor those of Thomas et al [11] implicate IgG as a major contributor to the HMW protein aggregates, though there was a shift in the molecular-weight distribu- …”
Section: Comparison Of Fviii Productscontrasting
confidence: 64%
“…It has been claimed, although not really proven, that purity is an important criterion of the quality of some therapeutic preparations to avoid unnecessary protein overload and, particularly, immunological disturbances after long-term administration [27,28]. The present purification method makes possible to recover a vWF solution which is highly purified as evidenced by the specific activity (345 U CBNmg protein), and confirmed by the immunonephelometric, electrophoretic and immunoblotting studies.…”
Section: Discussionmentioning
confidence: 64%